Optimum Stop Spacing for Accessibility - Wu, Hao; Levinson, David (European Journal of Transport and Infrastructure Research, 2021)
The cumulative opportunities measure accessibility is defined as the number of opportunities reachable under a given time threshold. The spacing between transit stations is fundamental for accessibility by transit, yet the stations cannot be easily relocated in built-up areas. This paper examines the relation between transit stop spacing and person-weighted accessibility for an urban train route through an analytical model, and identifies that for each type of transit (e.g., given some combination of vehicle acceleration, deceleration, top speed, dwell time, platform type), an optimal stop spacing exists that maximizes accessibility; neither short nor excessive stop spacing are efficient in providing accessibility. Rail is used as example, though the model and findings are applicable to bus services as well. This paper brings attention to the importance of stop spacing in accessibility, and provides guidelines for transit planning for the operational improvement of transit accessibility.